2005
DOI: 10.1073/pnas.0500679102
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 regulates Nemo-like kinase by mediating its interaction with IL-6-stimulated TGFβ-activated kinase 1 for STAT3 Ser-727 phosphorylation

Abstract: Signal transducer and activator of transcription 3 (STAT3) is activated by the IL-6 family of cytokines and growth factors. STAT3 requires phosphorylation on Ser-727, in addition to tyrosine phosphorylation on Tyr-705, to be transcriptionally active. In IL-6 signaling, the two major pathways that derive from the YXXQ and the YSTV motifs of gp130 cause Ser-727 phosphorylation. Here, we show that TGF-␤-activated kinase 1 (TAK1) interacts with STAT3, that the TAK1-Nemo-like kinase (NLK) pathway is efficiently act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
78
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 40 publications
1
78
0
Order By: Relevance
“…Recent evidence suggests that STAT3 serine phosphorylation, which occurs within a mitogen activated protein kinase (MAPK) consensus site (Ser727), has a positive role in STAT3 transcriptional activation (Shen et al 2004, Kojima et al 2005, Sun et al 2006. Indeed, extracellular signal-regulated protein kinases (ERKs) activation targets STAT3 serine phosphorylation (Kuroki & O'Flaherty 1999, O'Rourke & Shepherd 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that STAT3 serine phosphorylation, which occurs within a mitogen activated protein kinase (MAPK) consensus site (Ser727), has a positive role in STAT3 transcriptional activation (Shen et al 2004, Kojima et al 2005, Sun et al 2006. Indeed, extracellular signal-regulated protein kinases (ERKs) activation targets STAT3 serine phosphorylation (Kuroki & O'Flaherty 1999, O'Rourke & Shepherd 2002.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent study showed that TAB2 could also bridge TAK1 with its substrate, such as RCAN1 (36). In the TAK1-NLK cascade, TAK1 activates NLK, but these two proteins do not directly interact with each other (4,5). The finding that TAB2 can scaffold TAK1 and NLK fills the gap and declares the role of TAB2 in directing TAK1 signaling to its specific downstream effector.…”
Section: Wnt3a-conditioned Medium Enhances the Formation Of Tak1⅐tab2mentioning
confidence: 88%
“…TAK1 is regulated by several distinct extracellular stimuli as previously reported (8,(22)(23)(24). However, only some of them can stimulate the TAK1-NLK cascade (5). This notion suggests that some specific regulation might be required for the signal transduction from TAK1 to NLK.…”
mentioning
confidence: 79%
See 2 more Smart Citations